Post-Streptococcal Uveitis: Case Report. (3rd October 2019) - Medina, Carlos Augusto; Fajardo, Angela; Calderon, Ana; Aracena, Manuel
ABSTRACT: Background : Post-streptococcal uveitis is a rare ocular disease which is part of other auto-immune conditions associated with post-streptococcal syndrome. It was first mentioned in medical literature in 1991, with only a few cases published at that time. We are presenting the case of a patient with bilateral panuveitis subsequent to bacterial pharyngotonsillitis, with studies which had come back negative for other uveitis etiologies and which had responded very well to established treatment. Clinical Case : A case of post-streptococcal uveitis is presented with a review of current concepts of this rare eye disease.